Variegation and space weathering on asteroid 21 Lutetia - Schröder, S.E.; Keller, H. U.; Mottola, S.; Scholten, F.; Preusker, Frank; Matz, K.-D.; Hviid, S. (Planetary and Space Science, 2015)
During the flyby in 2010, the OSIRIS camera on-board Rosetta acquired hundreds of high-resolution images of asteroid Lutetia's surface through a range of narrow-band filters. While Lutetia appears very bland in the visible wavelength range, Magrin et al. (2012) tentatively identified UV color variations in the Baetica cluster, a group of relatively young craters close to the north pole. As Lutetia remains a poorly understood asteroid, such color variations may provide clues to the nature of its surface. We take the color analysis one step further. First we orthorectify the images using a shape model and improved camera pointing, then apply a variety of techniques (photometric correction, principal component analysis) to the resulting color cubes. We characterize variegation in the Baetica crater cluster at high spatial resolution, identifying crater rays and small, fresh impact craters. We argue that at least some of the color variation is due to space weathering, which makes Lutetia's regolith redder and brighter.